Aprendizagem móvel na formação continuada docente: um olhar sob a perpectiva dos princípios de comunidade de prática - Denise Alves Soares Veridiano (2019)
This study discusses the potentialities of using mobile technology devices, especially the WhatsApp application, in the professional development of Portuguese language teachers, under the Situated Learning (LAVE e WENGER, 1991) Communities of Practice (WENGER, 1998). Almeida and Araújo Jr. (2015); Royle et al (2014) and UNESCO (2014) point to the need for teacher training for the use of digital devices for educational purposes. The objectives are: (1) to identify characteristics of Community of Practice (CoP) and Legitimate Peripheral Participation during professional development via WhatsApp; (2) to seek empirical evidence of the potential of mobile applications, especially WhatsApp, for professional development of teachers; (3) check how familiarity with the features of mobile devices and the WhatsApp application influences the course participation process. Therefore, this research, through participant observation and case study, descriptive interpretive, has as context a group of 45 participants from an eight - week course, taught via WhatsApp - Taba Móvel Redigir - for the professional development of Portuguese language teachers; the content of the course addressed the use of the resources by the teacher and reflection on the pedagogical use. The research instruments are initial questionnaire, with the purpose of outlining the profile of the teachers participating in the course, such as age, resourcefulness with mobile devices, etc .; interactions between participants during the course; and final questionnaire, where one can verify observed aspects in the interactions, as well as, identify elements not clarified in the other means of investigation. The results indicate that, in the situation posed, by observing the principles of cultivation of CoP in the design of the course and mediation of the group, the Community of Practice emerged in the group Taba Móvel Redigir, because there were traces of mutual engagement, joint enterprise and shared repertoire. We noticed that, in the analyzed data, there was no interference from familiarity with mobile devices and participation in the course. And we also denote pertinence and potentiality of using the WhatsApp application as a professional development environment. Therefore, we believe that this research brings contributions to the area of Mobile Learning by proposing the fostering of Community of Practice in a group organized in WhatsApp and reflections of the potential of this app for learning; for the area of learning conceptions when approaching the notions of social learning theory - the basis of Community of Practice in terms of Lave and Wenger (1991) and Wenger (1999); and to the area of professional development when presenting conclusions about the possibility of courses in the formats discussed in this work.